Porous substrate reinforced anion exchange membrane as well as preparation method and application thereof
By using polyarylene alkylene cationic polymers in the anion exchange membrane and performing porous substrate enhancement, the problem of water absorption and swelling of the anion exchange membrane in the hydrated state is solved, and better mechanical properties and mechanical durability are achieved, while maintaining good electrochemical properties and chemical stability.
Patent Information
- Application Number
- CN202411703765.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing anion exchange membranes have too high water absorption and swelling in the hydrated state, resulting in poor performance in mechanical properties and mechanical durability.
Polyaryl alkylene cationic polymers are used as the electrolyte, and composite reinforcement is performed on the porous substrate to form a porous substrate-like structure-enhanced anion exchange membrane.
It improves the dimensional stability and mechanical properties of the anion exchange membrane, while maintaining good alkali stability and ionic conductivity, reducing the amount of cationic polymer, and has good cost-effectiveness.
Smart Images

Figure CN119529349A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anion exchange membranes, and in particular to a porous substrate reinforced anion exchange membrane and a preparation method and application thereof. Background Art
[0002] Hydrogen energy has outstanding advantages such as high energy density and zero pollution. Its use and development is one of the most feasible ways to solve energy and environmental problems. Anion exchange membrane fuel cells (AEMFC) and anion exchange membrane water electrolysis (AEMWE) are important carriers for the use and development of hydrogen energy. The alkaline working environment enables them to use non-precious metal catalysts and low-cost accessories. They are an important direction for future hydrogen energy conversion.
[0003] As a key material for AEMFC and AEMWE, it is of great significance to the development of anion exchange membranes with excellent mechanical properties, anti-swelling and mechanical durability. Good mechanical properties can ensure the smooth progress of anion exchange membranes from membrane electrode preparation to device assembly and operation. At present, due to the high ion content of cationic polymers, their water absorption and swelling in the hydrated state are too high, causing most AEMs to show low tensile strength and mechanical durability. Using porous substrates to composite reinforce cationic polymers is an effective strategy. The addition of porous substrates as a support can improve the overall mechanical properties of AEM, and the cationic polymers filled in microporous fibers are constrained by the substrate, and the swelling will be effectively inhibited. However, cationic polymers are usually hydrophilic compounds, and the commonly used porous substrates (such as polyethylene, expanded polytetrafluoroethylene, polyphenylene sulfide, polyetheretherketone, etc.) are hydrophobic materials, and the compatibility between the two is poor. In the reported preparation process, the porous reinforced substrate has been pre-treated in advance by using solvents such as ethanol and propanol to improve its hydrophilicity, but this strategy increases the membrane preparation process, and the rapid volatilization of alcohol solvents can easily lead to the failure of its hydrophilic treatment. Summary of the invention
[0004] The purpose of the present application is to provide a porous substrate reinforced anion exchange membrane and its preparation method and application, using a cheap porous base membrane as a reinforced substrate, using a polyarylene alkylene type cationic polymer as a filling electrolyte, and preparing a sandwich-like reinforced anion exchange membrane. The feature of the present invention is that a polyarylene alkylene type cationic polymer is selected as an electrolyte, and the anion exchange membrane prepared therefrom has relatively excellent alkali stability and ion conductivity, but its dimensional stability needs to be improved. When it is reinforced by a substrate, the obtained porous substrate reinforced anion exchange membrane not only retains the relatively excellent alkali stability and ion conductivity of the original membrane, but also has significantly improved dimensional stability and mechanical properties due to the constraint reinforcement of the porous substrate.
[0005] The present application provides a porous substrate reinforced anion exchange membrane, which has a sandwich-like structure, including a porous substrate arranged in the middle and cationic polymers arranged at the top and bottom, and the internal gaps of the porous substrate are filled with cationic polymers.
[0006] Preferably, the molecular structure of the cationic polymer is as follows:
[0007]
[0008] Wherein, n represents the degree of polymerization, and n is an integer between 10–1,000,000;
[0009] The Ar fragments are independently selected from the disubstituted fragment Ar1 and the polysubstituted fragment Ar2, and the molar ratio of the Ar2 fragment to the Ar1 fragment is r, and 0≤r≤1.0;
[0010] Ar1 is independently selected from one or more of the following structures:
[0011]
[0012] Ar2 is independently selected from one or more of the following structures:
[0013]
[0014] R 1 Independently selected from hydrogen atoms, hydrocarbon groups with 1-20 carbon atoms, or fully or partially fluorinated alkyl groups with 1-6 carbon atoms;
[0015] k = 0 or 1; x = 0–12;
[0016] Z is independently selected from one or more of a H atom, a quaternary ammonium cation and a nitrogen-containing heterocyclic cation.
[0017] Preferably, the quaternary ammonium cation has the formula:
[0018]
[0019] Among them, R 2 –R 7 independently selected from hydrocarbon groups having 1 to 20 carbon atoms, and R 2 and R 6 Can be connected between or within molecular chains; J = 0–3; counterion A - One or more selected from halide ions, methyl sulfate ions, hydroxide ions or bicarbonate ions.
[0020] Preferably, the nitrogen-containing heterocyclic cation comprises one or more of a partially or completely substituted pyrazole, pyrrole, piperidine, imidazole and quinine cation, having the following structure:
[0021]
[0022] Among them, R 81r -R 810 independently selected from hydrocarbon groups having 1 to 20 carbon atoms, the counterion A - One or more selected from halide ions, methyl sulfate ions, hydroxide ions or bicarbonate ions.
[0023] The preparation steps of the porous substrate reinforced anion exchange membrane are as follows:
[0024] S1, dissolving a cationic polymer in a first organic solvent to obtain a first cationic polymer solution;
[0025] S2, adding a second organic solvent to the first cationic polymer solution obtained in S1, and mixing them uniformly to obtain a second cationic polymer solution containing a cosolvent;
[0026] S3, applying the second cationic polymer solution containing the cosolvent obtained in S2 on the substrate for coating;
[0027] S4, laying a porous substrate on the upper surface of the coated substrate obtained in S3, and drying to obtain a single-side coated anion exchange membrane;
[0028] S5. Coating a second cationic polymer solution on the upper surface of the anion exchange membrane coated on one side obtained in S4, removing the solvent in a drying oven, and peeling off after drying to obtain a porous substrate reinforced anion exchange membrane.
[0029] Preferably, the first organic solvent used in S1 is a polar aprotic solvent such as at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylacetamide or N,N-dimethylformamide; the second organic solvent used in S2 is at least one of C1-C10 alcohol solvents.
[0030] Preferably, the amount of the second organic solvent added is 10-150 wt % of the first cationic polymer solution; and the solid content of the first cationic polymer solution is 10-40 wt %.
[0031] Preferably, the coating method used in S3 and S5 includes at least one of slit coating, scraper, wire rod, and micro-concave coating, and the coating thickness is 8-500 μm.
[0032] Preferably, the porous substrate used in S4 is at least one of polyethylene, polypropylene, expanded polytetrafluoroethylene, expanded polyvinylidene fluoride, polyphenylene sulfide, polyetheretherketone or nylon, and its thickness ranges from 3 to 100 μm.
[0033] The present application provides an application of the above-mentioned porous substrate reinforced anion exchange membrane in an alkaline membrane energy conversion device.
[0034] Therefore, the present application provides a porous substrate reinforced anion exchange membrane and a preparation method and application thereof, which have the following beneficial effects:
[0035] 1. The present invention uses polyarylene alkylene type cationic polymers, which themselves have high ionic conductivity and good alkali stability, to ensure that the enhanced membrane obtained after the porous substrate is enhanced still has good electrochemical properties and chemical stability;
[0036] 2. By adding C1-C10 alcohol solvents to the cationic polymer solution, the compatibility between the porous substrate and the cationic polymer solution is improved, and the cationic polymer solution can achieve good wetting and filling of the porous substrate, which simplifies the film-making process in actual production and is suitable for large-scale production. The addition of low-boiling-point alcohol solvents reduces the use of high-boiling-point solvents such as polar aprotic solvents such as N,N-dimethylformamide and dimethyl sulfoxide in the initial coating solution, which facilitates the subsequent solvent recovery and drying processes and effectively reduces production costs.
[0037] 3. The three-layer composite membrane prepared by the above preparation method has the same thickness of the upper and lower layers, which is convenient for subsequent production and assembly of the membrane.
[0038] 4. After being reinforced by the porous substrate, the composite membrane has higher mechanical strength and dimensional stability.
[0039] 5. The enhanced membrane reduces the amount of cationic polymer used and has better cost-effectiveness.
[0040] 6. The porous substrate-enhanced anion exchange membrane prepared by the present invention can be used in many fields such as alkaline membrane fuel cells and water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a SEM image of the anion exchange membrane in Example 1 of the present invention;
[0042] Figure 2 is a curve diagram showing the change of the hydroxide conductivity of the anion exchange membrane 2 in Example 1 of the present invention and Comparative Example 1 with the temperature;
[0043] Figure 3 is a curve diagram showing the change of water absorption rate of anion exchange membrane 1 in Example 1 of the present invention and Comparative Example 1 with temperature;
[0044] Figure 4 is a curve diagram showing the change in swelling rate of anion exchange membrane 1 in Example 1 of the present invention and Comparative Example 1 as a function of temperature;
[0045] Figure 5 is a comparison diagram of the mechanical properties of anion exchange membrane 1 in Example 1 of the present invention and Comparative Example 1;
[0046] Figure 6 is a fuel cell polarization curve diagram of anion exchange membrane 2 in Example 1 of the present invention;
[0047] Figure 7 This is a polarization curve diagram of the water electrolyzer of the anion exchange membrane 2 in Example 1 of the present invention. DETAILED DESCRIPTION
[0048] The technical solution of the present invention is further illustrated by the following examples.
[0049] Example 1
[0050] S1. Dissolve polymer electrolyte P1 (0.5 g) in 2.5 mL N,N-dimethylformamide and stir at room temperature until completely dissolved to obtain a cationic polymer P1 solution.
[0051] S2. Add 5.5 mL of methanol to the cationic polymer P1 solution obtained in S1, and mix well to obtain a cationic polymer solution in which the co-solvent is N,N-dimethylformamide / methanol and the solid content of the cationic polymer is 7%.
[0052] S3. Take the S2 cationic polymer solution and scrape it to form a cationic polymer layer with an area of 10 cm×10 cm on the coating substrate. Then, lay an expanded polytetrafluoroethylene porous substrate with a thickness of 11 μm on the upper surface, with an average pore size of 250 nm and a porosity of 80%, to obtain a single-side coated anion exchange membrane.
[0053] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P1-ePTFE with a thickness of 38 μm, wherein the thickness of the upper and lower cationic polymer layers is 13.5 μm respectively, and the thickness of the middle reinforcement layer is 11 μm.
[0054] The counter ion is Br - The porous substrate reinforced anion exchange membrane P1-ePTFE was immersed in a 2 mol / L NaCl solution for 24 h and then washed thoroughly with deionized water to obtain a counter ion of Cl - P1-ePTFE anion exchange membrane 1.
[0055] The counter ion is Br - The porous substrate reinforced anion exchange membrane P1-ePTFE was immersed in 2 mol / L NaOH solution for 48 h and then washed with deionized water to obtain a counter ion of OH - P1-ePTFE anion exchange membrane II.
[0056] The chemical structure of the cationic polymer P1 is as follows:
[0057]
[0058] Application Example 1
[0059] a. Anion exchange membrane fuel cell
[0060] The P1-ePTFE anion exchange membrane II in Example 1 was used with Pt / C as the cathode and anode catalysts, wherein the Pt loading was 0.5 mg cm -2 , membrane electrode was prepared by catalyst coating membrane technology and applied to H 2 -O 2 Fuel cell testing.
[0061] b. Anion exchange membrane water electrolyzer
[0062] The P1-ePTFE anion exchange membrane II in Example 1 was used with Pt / C as the cathode and anode catalysts, wherein the Pt loading was 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied to water electrolyzer testing.
[0063] Comparative Example 1
[0064] Preparation of intrinsic P1 anion exchange membrane
[0065] S1. Dissolve polymer electrolyte P1 (0.8 g) in 6.5 mL N,N-dimethylformamide, stir at room temperature until completely dissolved, then pour on the coating substrate for coating, and heat at 80°C for 24 hours to fully evaporate the solvent. After peeling off from the base film, an anion exchange membrane P1 with a thickness of 38 μm is obtained.
[0066] The counter ion is Br - The P1 anion exchange membrane was immersed in a 2 mol / L NaCl solution for 24 h and then washed thoroughly with deionized water to obtain a counter ion of Cl - The P1 anion exchange membrane is a
[0067] The counter ion is Br - The P1 anion exchange membrane was immersed in a 2 mol / L NaOH solution for 48 h and then washed thoroughly with deionized water to obtain a counter ion of OH.- P1 anion exchange membrane II.
[0068] Test Example 1
[0069] The P1-ePTFE anion exchange membranes 1 and 2 obtained in Example 1 and the P1 anion exchange membranes 1 and 2 obtained in Comparative Example 1 were subjected to some of the following tests to characterize their basic properties and make a comparison.
[0070] a. Characterization of membrane cross-section morphology
[0071] The P1-ePTFE anion exchange membrane II (1cm×3cm) was quenched with liquid nitrogen, and the quenched cross-section was treated with platinum sputtering and gold spraying using a Hitachi SU3500 sputtering instrument. At an acceleration voltage of 15.0 kV, a cross-sectional image of the sample was obtained using a SEM equipped with an EDS detector.
[0072] The fractured cross section of the P1-ePTFE anion exchange membrane was characterized by SEM. Figure 1 As shown in Figure 2, the thickness of the upper and lower cationic polymer layers in P1-ePTFE anion exchange membrane II is basically the same, about 13 μm, there is no obvious stratification and gap between the layers, and the middle reinforcement layer is well filled without obvious defects. b. Hydroxide ion conductivity
[0073] The four-electrode AC impedance method was used to measure the P1-ePTFE anion exchange membrane II and P1 anion exchange membrane II into 1cm×5cm strips, which were then clamped on a fixture and placed in a water tank filled with pure water. The electrodes were installed and connected to the electrochemical workstation. In the constant current mode (0.1mA), the scanning frequency range was 1MHz-100Hz. On the Bode curve, the frequency range where the impedance was stable was found, and then the resistance R of the anion exchange membrane was read on the corresponding curve.
[0074] The hydroxide ion conductivity is calculated by the following formula:
[0075]
[0076] Wherein, R is the resistance of the anion exchange membrane, L is the distance between the electrodes (1.0 cm), w is the width of the anion exchange membrane, and d is the thickness of the anion exchange membrane.
[0077] According to the hydroxide ion conductivity detected at different temperatures, the hydroxide ion conductivity of P1-ePTFE anion exchange membrane 2 and P1 anion exchange membrane 2 changes with temperature, as shown in Figure 2 At 80°C, the hydroxyl ion conductivity of P1-ePTFE reinforced membrane II reaches 190 mS·cm -1, compared with P1 anion exchange membrane II, the hydroxide ion conductivity increased slightly after adding the non-functionalized ePTFE matrix.
[0078] c. Water absorption and swelling rate
[0079] P1-ePTFE anion exchange membrane 1 and P1 anion exchange membrane 1 were cut into strips of 1 cm × 8 cm and fully dried in an oven. The weight of the dried anion exchange membrane was recorded as W. dry Then soak the anion exchange membrane in deionized water, take it out every 12 hours, wipe off the water on the surface, and record the weight W of the anion exchange membrane after soaking at different temperatures (30-80℃) wet .
[0080] The water absorption (WU) is calculated by the following formula:
[0081]
[0082] According to the calculated water absorption rates detected at different temperatures, the water absorption rate curves of P1-ePTFE anion exchange membrane 1 and P1 anion exchange membrane 1 with temperature are obtained, as shown in FIG. Figure 3 shown.
[0083] The swelling ratio (SR) is an important indicator to measure the dimensional stability of the membrane. It is measured by the length (L) of the dry and wet anion exchange membrane. dry ) and (L wet ) is calculated by the following formula:
[0084]
[0085] According to the calculated swelling ratios detected at different temperatures, the swelling ratio curves of P1-ePTFE anion exchange membrane 1 and P1 anion exchange membrane 1 with temperature were obtained, as shown in FIG. Figure 4 shown.
[0086] d. Determination of mechanical properties:
[0087] The electronic universal testing machine was used to test the -1 The tensile properties of the obtained P1-ePTFE anion exchange membrane 1 and P1 anion exchange membrane 1 were measured at a tensile speed. Both P1-ePTFE anion exchange membrane 1 and P1 anion exchange membrane 1 were cut into dumbbell shapes. Three parallel samples were set for each group of samples. The samples were balanced in the test environment for 24 hours before use. The test results are shown in Figure 5As shown, it can be seen that the tensile strength of P1-ePTFE anion exchange membrane 1 reaches 55MPa, and the elongation at break exceeds 110%, while the tensile strength of P1 anion exchange membrane 1 is only 35Mpa, and the elongation at break is less than 80%, which proves that the P1-ePTFE anion exchange membrane 1 reinforced with ePTFE has more excellent mechanical properties.
[0088] e. Determination of fuel cell performance
[0089] The P1-ePTFE anion exchange membrane II uses Pt / C as the cathode and anode catalysts, where the Pt loading is 0.5 mg cm -2 The membrane electrode was prepared by catalyst-coated membrane technology. At a gas flow rate of 300 mL min -1 , back pressure of 150 kPa, relative humidity of 100%, the electrochemical properties of the P1-ePTFE anion exchange membrane II in Example 1 were tested, as shown in FIG. Figure 6 As shown, it reaches 1.2W·cm -2 The maximum power density.
[0090] f. Determination of water electrolyzer performance
[0091] The P1-ePTFE anion exchange membrane II uses Pt / C as the cathode and anode catalysts, where the Pt loading is 0.5 mg cm -2 The membrane electrode was prepared by catalyst coating membrane technology. The water electrolyzer performance test was carried out at 80°C and 1M KOH solution to detect the water electrolyzer performance of the P1-ePTFE anion exchange membrane II in Example 1. Figure 7 shown.
[0092] In summary, at 80 °C, the hydroxyl ion conductivity of P1-ePTFE anion exchange membrane reaches 190 mS·cm -1 , with high water absorption, less than 10% in-plane swelling rate and excellent mechanical properties, it has good performance when applied to fuel cells. In an alkaline membrane water electrolyzer, it can reach 5.75Acm at 2V voltage. -2 high current density.
[0093] Example 2
[0094] S1. Dissolve polymer electrolyte P2 (0.7 g) in 2.0 mL N,N-dimethylformamide and stir at room temperature until completely dissolved to obtain a cationic polymer P1 solution.
[0095] S2. Add 7.5 mL of isopropanol to the cationic polymer P1 solution obtained in S1, and mix well to obtain a cationic polymer solution in which the co-solvent is N,N-dimethylformamide / isopropanol and the solid content of the cationic polymer is 8%.
[0096] S3. Take the S2 cationic polymer solution and scrape it to form a cationic polymer layer with an area of 10 cm×10 cm on the coating substrate. Then, lay a polyethylene porous substrate with a thickness of 8 μm on the upper surface, with an average pore size of 110 nm and a porosity of 45%, to obtain a single-side coated anion exchange membrane.
[0097] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P2-PE with a thickness of 40 μm, wherein the thickness of the upper and lower cationic polymer layers is 16 μm respectively, and the thickness of the middle reinforcement layer is 8 μm.
[0098] The counter ion is Br - The porous substrate-enhanced anion exchange membrane P2-PE was immersed in a 2 mol / L NaOH solution for 24 h and then washed thoroughly with deionized water to obtain a counter ion of OH - P2-PE anion exchange membrane.
[0099] The chemical structure of the cationic polymer P2 is as follows:
[0100]
[0101] Application Example 2
[0102] a. Anion exchange membrane fuel cell
[0103] The counter ion in Example 2 is OH - The P2-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , using catalyst coated membrane technology to prepare membrane electrodes for H 2 -O 2 Fuel cell testing.
[0104] b. Anion exchange membrane water electrolyzer
[0105] The counter ion in Example 2 is OH - The P2-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied in water electrolyzer tests.
[0106] Example 3
[0107] S1. Dissolve polymer electrolyte P3 (0.5 g) in 2.0 mL N,N-dimethylformamide and stir at room temperature until completely dissolved to obtain a cationic polymer P3 solution.
[0108] S2. Add 5.0 mL of isopropanol to the cationic polymer P1 solution obtained in S1, and mix well to obtain a cationic polymer solution in which the co-solvent is N,N-dimethylformamide / isopropanol and the solid content of the cationic polymer is 10%.
[0109] S3. Take the S2 cationic polymer solution and scrape it to form a cationic polymer layer with an area of 10 cm×20 cm on the coating substrate. Then, lay a polyethylene porous substrate with a thickness of 8 μm on the upper surface, with an average pore size of 110 nm and a porosity of 45%, to obtain a single-side coated anion exchange membrane.
[0110] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P3-PE with a thickness of 20 μm, wherein the thickness of the upper and lower cationic polymer layers is 6 μm respectively, and the thickness of the middle reinforcement layer is 8 μm.
[0111] The counter ion is Br - The porous substrate-reinforced anion exchange membrane P3-PE was immersed in a 2 mol / L NaOH solution for 24 h and then washed thoroughly with deionized water to obtain a counter ion of OH - P3-PE anion exchange membrane.
[0112] The chemical structure of the cationic polymer P3 is as follows:
[0113]
[0114] Application Example 3
[0115] a. Anion exchange membrane fuel cell
[0116] The counter ion in the above Example 3 is OH - The P3-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , using catalyst coated membrane technology to prepare membrane electrodes for H 2 -O 2 Fuel cell testing.
[0117] b. Anion exchange membrane water electrolyzer
[0118] The counter ion in the above Example 3 is OH- The P3-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied in water electrolyzer tests.
[0119] Example 4
[0120] S1. Dissolve polymer electrolyte P4 (0.55 g) in 3.0 mL of dimethyl sulfoxide and stir at room temperature until completely dissolved to obtain a cationic polymer P4 solution.
[0121] S2. Add 1.2 mL of n-butanol to the cationic polymer P4 solution obtained in S1, mix well to obtain a cationic polymer solution in which the co-solvent is dimethyl sulfoxide / n-butanol and the solid content of the cationic polymer is 12%.
[0122] S3. Take the S2 cationic polymer solution and scrape it to form a cationic polymer layer with an area of 8cm×10cm on the coating substrate. Then, lay an expanded polyvinylidene fluoride porous substrate with a thickness of 8μm on the upper surface, with an average pore size of 300nm and a porosity of 78%, to obtain a single-side coated anion exchange membrane.
[0123] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P4-ePVDF with a thickness of 38 μm, wherein the thickness of the upper and lower cationic polymer layers is 15 μm respectively, and the thickness of the middle reinforcement layer is 8 μm.
[0124] The counter ion is Br - The porous substrate-enhanced anion exchange membrane P4-ePVDF was immersed in a 2 mol / L NaOH solution for 24 h and then washed thoroughly with deionized water to obtain a counter ion of OH - P4-ePVDF anion exchange membrane.
[0125] The chemical structure of the above cationic polymer P4 is as follows:
[0126]
[0127] Application Example 4
[0128] a. Anion exchange membrane fuel cell
[0129] The counter ion in the above Example 4 is OH - The P4-ePVDF anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2, using catalyst coated membrane technology to prepare membrane electrodes for H 2 -O 2 Fuel cell testing.
[0130] b. Anion exchange membrane water electrolyzer
[0131] The counter ion in the above Example 4 is OH - The P4-ePVDF anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied in water electrolyzer tests.
[0132] Example 5
[0133] S1. Dissolve polymer electrolyte P5 (1.2 g) in 5.0 mL N,N-dimethylformamide and stir at room temperature until completely dissolved to obtain a cationic polymer P5 solution.
[0134] S2. Add 2.5 mL of isopropanol to the cationic polymer P5 solution obtained in S1, mix well to obtain a cationic polymer solution whose co-solvent is N,N-dimethylformamide / isopropanol and whose cationic polymer solid content is 15%.
[0135] S3. Take the S2 cationic polymer solution and scrape it to form a cationic polymer layer with an area of 16 cm×9 cm on the coating substrate. Then, lay a 10 μm thick expanded polytetrafluoroethylene porous substrate on the upper surface, with an average pore size of 250 nm and a porosity of 80%, to obtain a single-side coated anion exchange membrane.
[0136] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P5-ePTFE with a thickness of 70 μm, wherein the upper and lower cationic polymer layers are 30 μm thick respectively, and the middle reinforcement layer is 10 μm thick.
[0137] The counter ion is Br - The porous substrate reinforced anion exchange membrane P5-ePTFE was immersed in 2 mol / L NaOH solution for 24 h and then washed with deionized water to obtain a counter ion of OH - P5-ePTFE anion exchange membrane.
[0138] The chemical structure of the cationic polymer P5 is as follows:
[0139]
[0140] Application Example 5
[0141] a. Anion exchange membrane fuel cell
[0142] The counter ion in the above Example 5 is OH - P5-ePTFE anion exchange membrane with Pt / C as cathode and anode catalysts, where the Pt loading is 0.5 mg cm -2 , using catalyst coated membrane technology to prepare membrane electrodes for H 2 -O 2 Fuel cell testing.
[0143] b. Anion exchange membrane water electrolyzer
[0144] The counter ion in the above Example 5 is OH - P5-ePTFE anion exchange membrane with Pt / C as cathode and anode catalysts, where the Pt loading is 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied in water electrolyzer tests.
[0145] Example 6
[0146] S1. Dissolve polymer electrolyte P6 (0.6 g) in 4.0 mL N,N-dimethylformamide and stir at room temperature until completely dissolved to obtain a cationic polymer P6 solution.
[0147] S2. Add 2.0 mL of ethanol to the cationic polymer P6 solution obtained in S1, and mix well to obtain a cationic polymer solution in which the co-solvent is N,N-dimethylformamide / ethanol and the solid content of the cationic polymer is 10%.
[0148] S3. Take the S2 cationic polymer solution and scrape it to form a cationic polymer layer with an area of 20cm×10cm on the coating substrate. Then, lay a polyethylene porous substrate with a thickness of 7μm on the upper surface, with an average pore size of 80nm and a porosity of 45%, to obtain a single-side coated anion exchange membrane.
[0149] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P6-PE with a thickness of 27 μm, wherein the thickness of the upper and lower cationic polymer layers is 10 μm respectively, and the thickness of the middle reinforcement layer is 7 μm.
[0150] The counter ion is Br - The porous substrate-reinforced anion exchange membrane P6-PE was immersed in a 2 mol / L NaOH solution for 24 h and then fully washed with deionized water to obtain a counter ion of OH - P6-PE anion exchange membrane.
[0151] The chemical structure of the cationic polymer P6 is as follows:
[0152]
[0153] Application Example 6
[0154] a. Anion exchange membrane fuel cell
[0155] The counter ion in Example 6 is OH - The P6-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , using catalyst coated membrane technology to prepare membrane electrodes for H 2 -O 2 Fuel cell testing.
[0156] b. Anion exchange membrane water electrolyzer
[0157] The counter ion in Example 6 is OH - The P6-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied in water electrolyzer tests.
[0158] Example 7
[0159] S1. Dissolve polymer electrolyte P7 (0.5 g) in 3.2 mL of dimethyl sulfoxide and stir at room temperature until completely dissolved to obtain a cationic polymer P7 solution.
[0160] S2. Add 1.5 mL of ethanol to the cationic polymer P7 solution obtained in S1, and mix well to obtain a cationic polymer solution in which the co-solvent is dimethyl sulfoxide / ethanol and the solid content of the cationic polymer is 10.5%.
[0161] S3. Take the S2 cationic polymer solution and scrape it to form a cationic polymer layer with an area of 8cm×10cm on the coating substrate. Then, lay a 10μm thick expanded polytetrafluoroethylene porous substrate on the upper surface, with an average pore size of 250nm and a porosity of 80%, to obtain a single-side coated anion exchange membrane.
[0162] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P7-ePTFE with a thickness of 50 μm, wherein the upper and lower cationic polymer layers are 20 μm thick respectively, and the middle reinforcement layer is 10 μm thick.
[0163] The counter ion is Br - The porous substrate reinforced anion exchange membrane P7-ePTFE was immersed in 2 mol / L NaOH solution for 24 h and then washed with deionized water to obtain a counter ion of OH - P7-ePTFE anion exchange membrane.
[0164] The chemical structure of the cationic polymer P7 is as follows:
[0165]
[0166] Application Example 7
[0167] a. Anion exchange membrane fuel cell
[0168] The counter ion in Example 7 is OH - P7-ePTFE anion exchange membrane with Pt / C as cathode and anode catalysts, where the Pt loading is 0.5 mg cm -2 , using catalyst coated membrane technology to prepare membrane electrodes for H 2 -O 2 Fuel cell testing.
[0169] b. Anion exchange membrane water electrolyzer
[0170] The counter ion in Example 7 is OH - P7-ePTFE anion exchange membrane with Pt / C as cathode and anode catalysts, where the Pt loading is 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied in water electrolyzer tests.
[0171] Example 8
[0172] S1. Dissolve polymer electrolyte P8 (1.0 g) in 2.8 mL N,N-dimethylformamide and stir at room temperature until completely dissolved to obtain a cationic polymer P8 solution.
[0173] S2. Add 6.0 mL of isopropanol to the cationic polymer P8 solution obtained in S1, mix well to obtain a cationic polymer solution whose co-solvent is N,N-dimethylformamide / isopropanol and whose cationic polymer solid content is 11.5%.
[0174] S3, take S2 cationic polymer solution and scrape it to scrape out a cationic polymer layer with an area of 10cm×10cm on the coating substrate, and then lay a 20μm thick expanded polytetrafluoroethylene porous substrate on its upper surface, with an average pore size of 200nm and a porosity of 78%, to obtain a single-side coated anion exchange membrane.
[0175] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P8-ePTFE with a thickness of 80 μm, wherein the upper and lower cationic polymer layers are 30 μm thick respectively, and the middle reinforcement layer is 20 μm thick.
[0176] The counter ion is Br - The porous substrate reinforced anion exchange membrane P8-ePTFE was immersed in 2 mol / L NaOH solution for 24 h and then washed with deionized water to obtain a counter ion of OH - P8-ePTFE anion exchange membrane.
[0177] The chemical structure of the cationic polymer P8 is as follows:
[0178]
[0179] Application Example 8
[0180] a. Anion exchange membrane fuel cell
[0181] The counter ion in Example 8 is OH - P8-ePTFE anion exchange membrane with Pt / C as cathode and anode catalysts, where the Pt loading is 0.5 mg cm -2 , using catalyst coated membrane technology to prepare membrane electrodes for H 2 -O 2 Fuel cell testing.
[0182] b. Anion exchange membrane water electrolyzer
[0183] The counter ion in Example 8 is OH - P8-ePTFE anion exchange membrane with Pt / C as cathode and anode catalysts, where the Pt loading is 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied in water electrolyzer tests.
[0184] Example 9
[0185] S1. Dissolve polymer electrolyte P9 (0.8 g) in 3.0 mL N,N-dimethylformamide and stir at room temperature until completely dissolved to obtain a cationic polymer P9 solution.
[0186] S2. Add 2.0 mL of ethanol to the cationic polymer P8 solution obtained in S1, and mix well to obtain a cationic polymer solution in which the co-solvent is N,N-dimethylformamide / ethanol and the solid content of the cationic polymer is 15%.
[0187] S3. Take the S2 cationic polymer solution and scrape it to form a cationic polymer layer with an area of 15 cm×20 cm on the coating substrate. Then, lay a polyethylene porous substrate with a thickness of 7 μm on the upper surface, with an average pore size of 80 nm and a porosity of 45%, to obtain a single-side coated anion exchange membrane.
[0188] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P9-PE with a thickness of 25 μm, wherein the thickness of the upper and lower cationic polymer layers is 9 μm respectively, and the thickness of the middle reinforcement layer is 7 μm.
[0189] The counter ion is Br - The porous substrate-reinforced anion exchange membrane P9-PE was immersed in a 2 mol / L NaOH solution for 24 h and then washed thoroughly with deionized water to obtain a counter ion of OH - P9-PE anion exchange membrane.
[0190] The chemical structure of the cationic polymer P9 is as follows:
[0191]
[0192] Application Example 9
[0193] a. Anion exchange membrane fuel cell
[0194] The counter ion in Example 9 is OH - The P9-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , using catalyst coated membrane technology to prepare membrane electrodes for H 2 -O 2 Fuel cell testing.
[0195] b. Anion exchange membrane water electrolyzer
[0196] The counter ion in Example 9 is OH - The P9-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied in water electrolyzer tests.
[0197] Example 10
[0198] S1. Dissolve polymer electrolyte P10 (0.9 g) in 3.5 mL of dimethyl sulfoxide and stir at room temperature until completely dissolved to obtain a cationic polymer P10 solution.
[0199] S2. Add 5.0 mL of n-propanol to the cationic polymer P8 solution obtained in S1, mix well to obtain a cationic polymer solution in which the co-solvent is dimethyl sulfoxide / n-propanol and the solid content of the cationic polymer is 11%.
[0200] S3. Take the S2 cationic polymer solution and scrape it to form a cationic polymer layer with an area of 10 cm×10 cm on the coating substrate. Then, lay a polyethylene porous substrate with a thickness of 15 μm on the upper surface, with an average pore size of 80 nm and a porosity of 43%, to obtain a single-side coated anion exchange membrane.
[0201] S4. Coat the cationic polymer solution on the upper surface of the single-side coated anion exchange membrane obtained in S3, dry the solvent, and peel off the base membrane to obtain a porous substrate reinforced anion exchange membrane P10-PE with a thickness of 85 μm, wherein the thickness of the upper and lower cationic polymer layers is 35 μm respectively, and the thickness of the middle reinforcement layer is 15 μm.
[0202] The counter ion is Br - The porous substrate-reinforced anion exchange membrane P10-PE was immersed in a 2 mol / L NaOH solution for 24 h and then washed thoroughly with deionized water to obtain a counter ion of OH - P10-PE anion exchange membrane.
[0203] The chemical structure of the cationic polymer P10 is as follows:
[0204]
[0205] Application Example 10
[0206] a. Fuel Cell
[0207] The counter ion in the above Example 10 is OH - The P10-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , using catalyst coated membrane technology to prepare membrane electrodes for H 2 -O 2 Fuel cell testing.
[0208] b. Water electrolyzer
[0209] The counter ion in the above Example 10 is OH -The P10-PE anion exchange membrane uses Pt / C as the cathode and anode catalysts, with a Pt loading of 0.5 mg cm -2 , membrane electrodes were prepared using catalyst coated membrane technology and applied in water electrolyzer tests.
[0210] Therefore, the present invention provides a porous substrate enhanced anion exchange membrane and its preparation method and application. Directly adding a certain amount of alcohol solvent to the cationic polymer solution can greatly improve its compatibility with the porous substrate, so as to achieve efficient infiltration of the cationic polymer in the porous substrate. This method effectively simplifies the membrane-making process in actual production and is suitable for large-scale production. In addition, the addition of low-boiling-point alcohol solvents reduces the use of polar non-protonic solvents such as N,N-dimethylformamide and dimethyl sulfoxide and other high-boiling-point solvents in the initial coating solution, which is convenient for subsequent solvent recovery and drying processes, and effectively reduces production costs. The present invention uses the above structure as a porous substrate enhanced anion exchange membrane filled with polymer electrolytes, which has good electrochemical properties, dimensional stability and excellent mechanical properties, and has good application prospects in alkaline membrane energy conversion devices. A method for preparing a porous substrate enhanced anion exchange membrane has a simple and continuous production process and a low production cost, and is suitable for large-scale continuous production.
[0211] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.
[0212] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A porous substrate reinforced anion exchange membrane, characterized in that: The anion exchange membrane has a sandwich-like structure, which includes a porous substrate arranged in the middle and cationic polymers arranged at the top and the bottom, and the internal gaps of the porous substrate are filled with the cationic polymers.
2. A porous substrate reinforced anion exchange membrane according to claim 1, characterized in that: The molecular structure of the cationic polymer is shown below: Wherein, n represents the degree of polymerization, and n is an integer between 10–1,000,000; The Ar fragments are independently selected from the disubstituted fragment Ar1 and the polysubstituted fragment Ar2, and the molar ratio of the Ar2 fragment to the Ar1 fragment is r, and 0≤r≤1.0; Ar1 is independently selected from one or more of the following structures: Ar2 is independently selected from one or more of the following structures: R 1 Independently selected from hydrogen atoms, hydrocarbon groups with 1-20 carbon atoms, or fully or partially fluorinated alkyl groups with 1-6 carbon atoms; k = 0 or 1; x = 0–12; Z is independently selected from one or more of a H atom, a quaternary ammonium cation and a nitrogen-containing heterocyclic cation.
3. A porous substrate reinforced anion exchange membrane according to claim 2, characterized in that: The quaternary ammonium cation has the formula: Among them, R 2 –R 7 independently selected hydrocarbon groups having 1-20 carbon atoms, and R 2 and R 6 Can be connected between or within molecular chains; J = 0–3; counterion A - One or more selected from halide ions, methyl sulfate ions, hydroxide ions or bicarbonate ions.
4. A porous substrate reinforced anion exchange membrane according to claim 2, characterized in that: The nitrogen-containing heterocyclic cation comprises one or more of a partially or completely substituted pyrazole, pyrrole, piperidine, imidazole and quinine cation, and has the following structure: Among them, R 81 –R 810 independently selected from hydrocarbon groups having 1 to 20 carbon atoms, the counterion A - One or more selected from halide ions, methyl sulfate ions, hydroxide ions or bicarbonate ions.
5. A method for preparing a porous substrate reinforced anion exchange membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, dissolving a cationic polymer in a first organic solvent to obtain a first cationic polymer solution; S2, adding a second organic solvent to the first cationic polymer solution obtained in S1, and mixing them uniformly to obtain a second cationic polymer solution containing a cosolvent; S3, applying the second cationic polymer solution containing the cosolvent obtained in S2 on the substrate for coating; S4, laying a porous substrate on the upper surface of the coated substrate obtained in S3, and drying to obtain a single-side coated anion exchange membrane; S5. Coating a second cationic polymer solution on the upper surface of the anion exchange membrane coated on one side obtained in S4, removing the solvent in a drying oven, and peeling off after drying to obtain a porous substrate reinforced anion exchange membrane.
6. The method for preparing a porous substrate-reinforced anion exchange membrane according to claim 5, characterized in that: The first organic solvent used in S1 is a polar aprotic solvent such as at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylacetamide or N,N-dimethylformamide; the second organic solvent used in S2 is at least one of C1-C10 alcohol solvents.
7. The method for preparing a porous substrate-reinforced anion exchange membrane according to claim 5, characterized in that: The amount of the second organic solvent added is 10-150 wt % of the first cationic polymer solution; the solid content of the first cationic polymer solution is 10-40 wt %.
8. The method for preparing a porous substrate-reinforced anion exchange membrane according to claim 5, characterized in that: The coating method used in S3 and S5 includes at least one of slit coating, scraper, wire rod, and micro-concave coating, and the coating thickness is 8-500 μm.
9. The method for preparing a porous substrate-reinforced anion exchange membrane according to claim 5, characterized in that: The porous substrate used in S4 is at least one of polyethylene, polypropylene, expanded polytetrafluoroethylene, expanded polyvinylidene fluoride, polyphenylene sulfide, polyetheretherketone or nylon, and its thickness ranges from 3 to 100 μm.
10. Use of a porous substrate reinforced anion exchange membrane according to any one of claims 1 to 4 in an alkaline membrane energy conversion device.
Citation Information
Patent Citations
Preparation method of alkaline anion exchange membrane fuel cell membrane electrode
CN109921031A
Cation exchange membrane with screen cloth reinforced flat-plate-type porous membrane as substrate and manufacturing method of cation exchange membrane
CN110227561A
Preparation method of ultrathin composite anion exchange membrane
CN113583278A
Cross-linked composite anion exchange membrane as well as preparation method and application thereof
CN118206801A
Anion exchange membrane and method for manufacturing same
WO2024128453A1
Cited By
Enhanced anion exchange membrane based on microporous skeleton and integrated membrane electrode
CN120453430A
An enhanced anion exchange membrane based on a microporous framework and an integrated membrane electrode
CN120453430B
High-alkali-resistance pyrazole cationic compound, high-alkali-resistance pyrazole cationic polymer as well as preparation method and application of high-alkali-resistance pyrazole cationic compound
CN121181477A
Anion exchange membrane and preparation method therefor, and water electrolysis hydrogen production device
WO2026201012A1